Physiology of the heart - Katz, Arnold M. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins Health, 2011)
"Dr. Arnold Katz's internationally acclaimed classic is now in its thoroughly revised Fifth Edition, incorporating the latest molecular biology research and extensively exploring the clinical applications of these findings. In the single authored, expert voice that is this book's unique strength, Dr. Katz provides a comprehensive overview of the physiological and biophysical basis of cardiac function, beginning with structure and proceeding to biochemistry, biophysics, and pathophysiology in arrhythmias, ischemia, and heart failure. Emphasis is on the interrelationships of basic processes among the cell, cardiac muscle function, and the biophysics of contractile and electrical behavior. This edition includes new material on cell signaling and molecular biology"--Provided by publisher.
1. Structure of the Heart and Cardiac Muscle 2. Energetics and Energy Production 3. Energy Utilization (Work and Heat) 4. The Contractile Proteins 5. The Cytoskeleton 6. Active State, Length-Tension Relationship, Cardiac Mechanics 7. Excitation-Contraction Coupling: Extracellular and Intracellular Calcium Cycles 8. Signal Transduction: Functional Signaling 9. Signal Transduction: Proliferative Signaling 10. Regulation of Cardiac Muscle Performance 11. The Heart as a Muscular Pump 12. The Working Heart 13. Cardiac Ion Channels 14. The Cardiac Action Potential 15. The Electrocardiogram 16. Arrhythmias 17. The Ischemic Heart 18. Heart Failure.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Heart -- Physiology; Heart -- Pathophysiology; Electronic books